Aktivitas Manusia dan Distribusi Banteng (Bos Javanicus D’alton 1832) di Taman Nasional Alas Purwo - Muhammad Ali Imron; Jefri Oloan Sinaga (Fakultas Kehutanan Universitas Gadjah Mada, 2007)
Human Activities and Distribution of Banteng (Bos Javanicus D’alton 1832) in Alas Purwo National ParkThis study aims to comprehend whether human activities contribute to the presence of banteng (Bos sundaicus d’Alton 1836) in the Alas Purwo National Park (APNP). We laid continuous strip line transects from centre of human activities to the direction of core area of APNP. Three locations were selected: Sadengan grazing area, Giri Salaka Hinduism praying area, and Kutorejo village; representing low to high human disturbance respectively. We collected both direct and indirect presence of banteng as well as human activities within 20 metre strip lines with 10 metre width. Data were compiled each 100 metres and analyzed with means comparison to observe difference among locations. Correlation analyses were used to assess the relation between distance from centre of human activities, human activities and banteng presence. Regression analysis was used when significant correlations found.Our non parametric test showed that human disturbances are significantly different among sites (Kruskal Wallis Test; df 2 = 6.220, p< 0.05). In similar tendency but different manner, it is showed that the different levels of human disturbance conveyed significant difference in number of banteng’s tracks (Kruskal Wallis Test; df 2 = 18.888, p< 0.05). The distance from centre of human activities is negatively related to number of human tracks (Spearman rho; r2= -0.307 N= 64, p<0.05*) and also to number of banteng’s tracks (Spearman rho, r2= -0.728 N= 30, p<0.05**). The regression analysis showed that number of human tracks explained 18.6% of total variation on number of Banteng’s tracks, while distance from centre of human activities explained 59%.